The nucleotide addition cycle of the SARS-CoV-2 polymerase - Bera, Subhas Chandra; Seifert, Mona; Kirchdoerfer, Robert N.; Van Nies, Pauline; Yibulayin, Wubulikasimu; Quack, Salina; Papini, Flavia S.; Arnold, Jamie J.; Canard, Bruno; Cameron, Craig E.; Depken, Martin; Dulin, David (Cell Reports, 2021)
Coronaviruses have evolved elaborate multisubunit machines to replicate and transcribe their genomes. Central to these machines are the RNA-dependent RNA polymerase subunit (nsp12) and its intimately associated cofactors (nsp7 and nsp8). We use a high-throughput magnetic-tweezers approach to develop a mechanochemical description of this core polymerase. The core polymerase exists in at least three catalytically distinct conformations, one being kinetically consistent with incorporation of incorrect nucleotides. We provide evidence that the RNA-dependent RNA polymerase (RdRp) uses a thermal ratchet instead of a power stroke to transition from the pre- to post-translocated state. Ultra-stable magnetic tweezers enable the direct observation of coronavirus polymerase deep and long-lived backtracking that is strongly stimulated by secondary structures in the template. The framework we present here elucidates one of the most important structure-dynamics-function relationships in human health today and will form the grounds for understanding the regulation of this complex.
CRIS-Team Scopus Importer:2021-09-10
Keywords: backtracking; high-throughput/ultra-stable magnetic tweezers; nucleotide addition cycle; polymerase mechanochemistry; SARS-CoV-2 polymerase; single-molecule biophysics